Dual Sustainability in Agricultural Development: A Case-Based Framework From Bulgaria - Petrov, Daniel (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Sustainable nitrogen management remains a major challenge for Bulgarian agriculture, where low Nitrogen Use Efficiency (NUE) and limited uptake of innovative fertilization practices constrain productivity and environmental performance. This study aims to assess both the technological effectiveness and institutional enabling conditions for adopting urease inhibitors—specifically N-(n-butyl)thiophosphoric triamide (NBPT) and N-propyl-thiophosphoric triamide (NPPT)—within a real production context. A mixed-method approach was applied, combining a quantitative case analysis of a representative wheat farm with a documentary review of national policies, regulations and support programs. The results show an 8.1% increase in yield, a 23.4% improvement in NUE, and a higher Return on Investment (ROI) for inhibitor-treated plots, confirming the internal economic and agronomic sustainability of the technology. However, institutional assessment reveals critical constraints, including missing subsidy instruments, partial regulatory clarity, and weak advisory support structures, which limit broader adoption. To integrate these findings, the study employs a dual sustainability framework that evaluates both technological performance and institutional capacity. The conclusions highlight that technological innovations alone cannot drive agricultural transformation without coherent, well-aligned governance and support systems. Strengthening policy design, advisory services and regulatory instruments is essential for enabling the large-scale diffusion of effective nitrogen management technologies.